Promotion of livelihood opportunities to address food insecurity in Rohingya refugee camps of Bangladesh - Afsana Anwar; ARM. Mehrab Ali; Uday Narayan Yadav; Md. Nazmul Huda; Abu Ansar Md. Rizwan; Ateeb Ahmad Parray; Haribondhu Sarma; Oumma Halima; Nobonita Saha; Suvasish Das Shuvo; Probal Kumar Mondal; Abu Ahmed Shamim; et al. (Taylor & Francis Group, 2024)
ABSTRACTThe world is facing a tremendous problem in the form of food insecurity that is posing a great challenge to achieving sustainable development goal 2 of creating a hunger-free world. Refugees and displaced populations are particularly vulnerable to food insecurity and malnutrition, who lack any productive assets and depend on aid. Rohingya refugees, displaced from Myanmar and took refuge in Cox's Bazar, Bangladesh, live in a crowded unhealthy environment and are severely vulnerable to food insecurity and malnutrition. In our recent study, we found that only 21.6% of the households in Rohingya refugee camps had acceptable food security status. Interestingly, this study further revealed that acceptable food security status was significantly higher among the households that had some additional income aside from aid, compared to those relying on aid alone. This shows the importance of promoting livelihood opportunities to improve food security status among the camp dwellers. In this paper, we presented our views on promoting livelihood opportunities to address the overwhelming food insecurity crisis among the Rohingya refugees in Bangladesh.